small industrial cities. Heritage update. Tatiana Bystrova. Review - Mariya S. Frolova (Управление культурой)
Working with the historical and cultural heritage in the small industrial cities of the Urals, inscribed in the landscape and connected by a dense, historically established system of settlement, is a condition for their survival and development. The author shows the foundations of the stability of this system, the specifics of the architecture of industrial buildings and complexes, and the everyday culture of the region.The methods and cases of work with historical and cultural heritage introduced into scientific circulation in different regions of the world are selected taking into account the current economic, demographic, social processes in small Russian cities, which increases the efficiency of their possible use. The book is addressed to historians, architects, urbanists, designers involved in the actualization and rehabilitation of cultural heritage in industrial cities, students, employees of regional and municipal administrations, as well as everyone who is interested in this topic.